Report on industrial attachment with ADC Technologies Intel Pte Ltd - Zhang, Hong Yao (2008)
This report outlines the two projects undertaken during the IA period, explaining the requirements for the projects, the technical knowledge needed as well as invaluable knowledge acquired during the course of completing the two projects.